Full factorial and experimental investigation on surface integrity of stainless steel in wedm operation - Asmalina, Mohamad (2010)
Surface integrity generally can be described by its topological, mechanical, and metallurgical. Since the defects produced from different machining can affect the performance of component, experiments always will be conducted to understand the effect of changing operating parameters before new machining strategies are accepted. In this study, surface integrity was characterized by surface roughness and microhardness of stainless steel 304. The objectives of the project are investigating wire cut EDM parameters effect on surface roughness, and microhardness of stainless steel. Five cutting parameters selected to study their effects on surface integrity which are wire speed, wire tension, on time, off time, and peak current. The results show the relationship between parameters and surface roughness, and parameters and microhardness. The graph is being plotted using Minitab.